Evaluation of antioxidant capacity and physicochemical properties of Sudanese baobab (Adansonia digitata) seed-oil - Babiker, Sara; Mirghani, Mohamed Elwathig Saeed; Matar, Saleh M.; Kabbashi, Nassereldeen Ahmed; Alam, Md Zahangir; Marikkar, Mohammed Nazrim (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
The oil quality parameters of the seed oil of Baobab (Adansonia digitata) were evaluated using standard methods of analysis. The Iodine value, Peroxide value, Saponification value were 86 g/100g, 4.08 mEq/Kg, 188 mg/g, respectively, for seed oil. The oil content of the kernel was higher 23% compared to the hulls that contain 5.4% oil. The kernel oil contains substantial quantities of calcium, potassium, and magnesium, which were found to be 4116, 2339 and 1629 mg/Kg, respectively. The fatty acid profile showed that oleic and linoleic were the major unsaturated fatty acids, whereas palmitic was the major saturated acid. The oil also, showed considerable amount of total phenolic content (TPC) and worthy antioxidant activity. Baobab oil has great nutritional and industrial potentials. It is therefore recommended that more and advanced research should be undertaken for this abundant source of natural nutritious oil.